Combustion and Emission Characteristics of Variable Compression Ignition Engine Fueled with Jatropha curcas Ethyl Ester Blends at Different Compression Ratio. (16th April 2014) - Kumar, Rajneesh; Dixit, Anoop Kumar
Abstract : Engine performance and emission characteristics of unmodified biodiesel fueled diesel engines are highly influenced by their ignition and combustion behavior. In this study, emission and combustion characteristics were studied when the engine operated using the different blends (B10, B20, B30, and B40) and normal diesel fuel (B0) as well as when varying the compression ratio from 16.5 : 1 to 17.5 : 1 to 18.5 : 1. The change of compression ratio from 16.5 : 1 to 18.5 : 1 resulted in 27.1%, 27.29%, 26.38%, 28.48%, and 34.68% increase in cylinder pressure for the blends B0, B10, B20, B30, and B40, respectively, at 75% of rated load conditions. Higher peak heat release rate increased by 23.19%, 14.03%, 26.32%, 21.87%, and 25.53% for the blends B0, B10, B20, B30, and B40, respectively, at 75% of rated load conditions, when compression ratio was increased from16.5 : 1 to 18.5 : 1. The delay period decreased by 21.26%, CO emission reduced by 14.28%, andNO x emission increased by 22.84% for B40 blends at 75% of rated load conditions, when compression ratio was increased from 16.5 : 1 to 18.5 : 1. It is concluded that Jatropha oil ester can be used as fuel in diesel engine by blending it with diesel fuel.